A predominance of hypertensive heart failure in the Abuja heart study cohort of urban Nigerians: a prospective clinical registry of 1515 de novo cases. (2012)
Aims: Even though cardiovascular disease is gradually becoming the major cause of morbidity and mortality in sub-Saharan Africa, there are very few data on the pattern of heart disease in this part of the world. We therefore decided to determine the pattern of heart disease in Abuja, which is one of the fastest growing and most westernized cities in Nigeria, and compare our findings with those of the Heart of Soweto Study in South Africa. Methods and results: Detailed clinical data were consecutively captured from 1515 subjects of African descent, residing in Abuja, and equivalent Soweto data from 4626 subjects were available for comparison. In Abuja, male subjects were on average, 2 years older than female subjects. Hypertension was the primary diagnosis in 45.8% of the cohort, comprising more women than men [odds ratio (OR) 1.96, 95% confidence interval (CI) 1.26– 2.65], and hypertensive heart failure (HF) was the most common form of HF in 61% of cases. On an age- and sex-adjusted basis, compared with the Soweto cohort, the Abuja cohort were more likely to present with a primary diagnosis of hypertension (adjusted OR 2.10, 95% CI 1.85– 2.42) or hypertensive heart disease/failure (OR 2.48, 95% CI 2.18–2.83); P , 0.001 for both. They were, however, far less likely to present with CAD (OR 0.04, 95% CI 0.02 –0.11) and right heart failure (2.5% vs. 27%). Conclusion: As in Soweto, but more so, hypertension is the most common cause of de novo HF presentations in Abuja, Nigeria.